(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Airbnb is an online marketplace that allows people to list and book unique places to stay around the world. Airbnb connects hosts who want to rent out their space with guests who are looking for more affordable and personalized accommodations than hotels.